Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1017/s0373463320000533
|View full text |Cite
|
Sign up to set email alerts
|

Application of colour combinations on visual search tasks under vibration environments

Abstract: Colour is widely utilised as a visual coding system in visual search, but its application under vibration conditions (e.g., in various vehicles) has not been fully explored. This study was designed to examine the effect of colour combinations on performance of visual search tasks conducted in vibration conditions. Forty-eight university students participated in an experiment where they were required to identify target type and location under 24 colour combinations (half in negative polarity and half in positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Individuals under vibration scenarios usually required extra efforts to maintain physical balance (Graham, 1990; Wertheim, 1998) and may suffer dizziness, discomfort, disturbance, and activity interference (Newell & Mansfield, 2006; Stevens & Parsons, 2002; Sundström, 2006; Tao et al, 2021; Wang et al, 2020). These consequences of vibration may degrade the efficiency of performing tasks when using input devices/fingers to point and drag with GUIs.…”
Section: Related Workmentioning
confidence: 99%
“…Individuals under vibration scenarios usually required extra efforts to maintain physical balance (Graham, 1990; Wertheim, 1998) and may suffer dizziness, discomfort, disturbance, and activity interference (Newell & Mansfield, 2006; Stevens & Parsons, 2002; Sundström, 2006; Tao et al, 2021; Wang et al, 2020). These consequences of vibration may degrade the efficiency of performing tasks when using input devices/fingers to point and drag with GUIs.…”
Section: Related Workmentioning
confidence: 99%
“…The above discussion suggests that, contrary to the assumption concerning a benefit of shields over white markings, an opposite pattern, of advantage for the white over shields, was detected. This may be explained by the human visual system’s sensitivity to high contrasts ( Wang et al, 2021 ), suggesting that white over black is more salient then red over black. This explanation fits the findings of a study reporting a benefit for white delineators over many other colors ( Abou-Senna et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…They studied eye movement data, collected from experienced port pilots operating on three different models of ECDIS, and found a significant difference between the participant port pilots and expert users. Wang et al (2020) examined the effect of colour combinations on performance of visual search tasks and found that colour combination significantly affected response time of the participants while not having a significant effect on their performance. They recommended colour combinations with negative polarity (e.g., yellow on black and white on black) for presenting search interfaces.…”
Section: Resultsmentioning
confidence: 99%